Profile of effective teaching [videorecording]. Special education - Silver, Jon.; Moir, Ellen; Moore, Sydnie; New Teacher Center (Santa Cruz, California). (Santa Cruz, Calif. New Teacher Center, 2005)
"Powerful integration of instructional strategies, classroom scenes include: inquiry and project-based learning, use of multicultural literature, physical movement embedded in lessons, integrating different learning modalities, SDAIE techniques, balance literacy program, infusing the arts throughout the curriculum, student centered learning environment."
"Dynamic instruction in a successful classroom."--Container cover.
"Featuring Sydnie Moore and her 3rd-5th grade special education class."
Keywords: Special education teachers -- Training of; Special education -- California -- Case studies; Teaching demonstrations